2000
DOI: 10.1046/j.1365-2605.2000.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenic disturbance induced by di‐(2‐ethylhexyl) phthalate is significantly prevented by treatment with antioxidant vitamins in the rat

Abstract: Phthalate esters, now regarded as endocrine disruptors, are widely used in the plastics industry. In particular, di-(2-ethylhexyl) phthalate (DEHP) is produced in large quantities, and is used in blood storage bags, catheters and haemodialysis instruments. Previous studies have demonstrated that treatment of rats with DEHP induces testicular atrophy with liver enlargement, although the precise nature and mechanism of the action of DEHP on these organs remains unclear. In the present study, we produced an exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 40 publications
5
43
0
Order By: Relevance
“…Curcumin and kolaviron may thus prevent peroxidative changes in the sperm and the testicular membrane, thus enhancing sperm motility and decreasing spermatozoa abnormalities. Our results are in agreement with Ishihara et al [5] who reported the protective effect of antioxidant vitamins on di-ethyl-hexylphthalate-induced testicular atrophy, a similar phthalate ester. In addition, co-administration of kolaviron and curcumin might have relieved the inhibition of the antioxidant enzymes, reduction of testosterone, G6PD and γ-GT, and/or may have triggered their synthesis that in turn attenuated the oxidative damage caused by DBP or its metabolites.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Curcumin and kolaviron may thus prevent peroxidative changes in the sperm and the testicular membrane, thus enhancing sperm motility and decreasing spermatozoa abnormalities. Our results are in agreement with Ishihara et al [5] who reported the protective effect of antioxidant vitamins on di-ethyl-hexylphthalate-induced testicular atrophy, a similar phthalate ester. In addition, co-administration of kolaviron and curcumin might have relieved the inhibition of the antioxidant enzymes, reduction of testosterone, G6PD and γ-GT, and/or may have triggered their synthesis that in turn attenuated the oxidative damage caused by DBP or its metabolites.…”
Section: Discussionsupporting
confidence: 94%
“…The exact mechanisms involved in the formation of phthalate-induced testicular atrophy are not known, but recently it was shown that administration of antioxidant vitamins together with di-ethyl-hexylphthalate prevented phthalate ester-induced testicular atrophy in rats [5] suggesting that the formation of reactive oxygen species may be involved in the formation of testicular atrophy in phthalate-exposed rats.…”
mentioning
confidence: 99%
“…Such products contain numerous chemicals, at least two of which (various types of parabens or phthalates) have been implicated in potentially causing adverse effects on testosterone and/or sperm production in animal studies (e.g. David et al 2000;Ishihara et al 2000;Oishi 2001Oishi , 2002, although for phthalates such effects have only been found after exposure to extremely high levels (500 -1500 mg kg 21 d…”
Section: Effects Of Environmental Chemicals On Spermatogenesis In Adumentioning
confidence: 99%
“…The treatment with the water extract of cumin plant (200 mg/kg B.W.) showed a significant decrease in testicular lipid hormone compared with the control group [31]. Effect of different treatments of the total content of sperms in the epididymis: It is noted from Figure (4) that there is a significant decrease in the treatment group with H2O2, the total number of sperm compared with the control.…”
Section: Tikrit Journal Of Pure Science 23 (3) 2018 Issn: 1813 -1662 mentioning
confidence: 91%
“…showed that the sperm cells were very effective compared to the control group (fig. 5-G &H), this may be due to the active substances contained in this plant that have resulted in a nonpositive result [31,33]. The result of histological section of the testes in the rats treated with vitamin E and H2O2 observed repair of the cells lining the seminiferous tubules with the continuation of the formation of sperm as shown in the figure (5-I&J) and this is agree with the result of [35] which observed that rats treated with vitamin E with fluoxetine showed an improvement in semeniferous tubules and an increase in the number of sperm.…”
Section: Histological Effect Of Different Treatment On Testismentioning
confidence: 99%